InSilico structure based designing of dihydrofolate reductase enzyme antagonists and potential small molecules that target DHFR protein to inhibit the folic acid biosynthetic pathways - Hossain, Md. Sameer (BRAC Univeristy, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.